2022
DOI: 10.1021/acs.chemmater.1c03450
|View full text |Cite
|
Sign up to set email alerts
|

Repeatable Photoinduced Insulator-to-Metal Transition in Yttrium Oxyhydride Epitaxial Thin Films

Abstract: Currently, no known material retains its photoinduced metallic conductivity over a long time while also exhibiting repeatable metal-to-insulator recovery. Here, we demonstrate such a highly repeatable photoinduced insulator-to-metal transition in yttrium oxyhydride (YO x H y ) epitaxial thin films. The temperature (T) dependence of the electrical resistivity (ρ) of the films transforms from the insulating to the metallic state (dρ/dT > 0) under ultraviolet laser illumination. The YO x H y film recovers its or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…On the other hand, there can be a large difference in the properties of octahedral versus tetrahedral H – , making the decrease in the population of certain H – potentially significant for the observed properties of the material. Not only are the octahedral H – likely the first to leave the structure upon oxidation, , but they are often cited as more mobile than tetrahedral H – either due to the lower formation energy for an octahedral H vacancy or their weaker electrostatic interactions with O 2– (more distance) . Having these mobile H – could be an essential ingredient to the formation and dissolution of a “darkened” phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, there can be a large difference in the properties of octahedral versus tetrahedral H – , making the decrease in the population of certain H – potentially significant for the observed properties of the material. Not only are the octahedral H – likely the first to leave the structure upon oxidation, , but they are often cited as more mobile than tetrahedral H – either due to the lower formation energy for an octahedral H vacancy or their weaker electrostatic interactions with O 2– (more distance) . Having these mobile H – could be an essential ingredient to the formation and dissolution of a “darkened” phase.…”
Section: Resultsmentioning
confidence: 99%
“… 5 , 7 One explanation for photochromism has emerged involving a structural rearrangement, 8 , 9 perhaps by local diffusion, 10 to segregate a metallic phase 1 , 11 , 12 of high H – content. 7 , 11 , 12 On the other hand, some suggest the formation of in-gap states by H 2 13 or OH – 14 generation as well as H – exchange between phases. 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published works [17,21] have shown that epitaxial thin films of YHO (originally insulating) exhibit metal-like temperature dependence of resistivity after UV laser exposure. In our study, polycrystalline YHO thin films photodarkened by 455 nm LED have showed similar behavior, that is, the resistance of the photodarkened film increased with temperature as expected for a metal (see Figure S2, Supporting Information).…”
Section: Temperature Dependencementioning
confidence: 99%
“…Furthermore, hydrogen may exist in three different charge states, i.e., positive H + , neutral H 0 , and negative H – . The hydrogen charge states in hydrogen-containing materials play a major role in their physical, mechanical, and electrochemical properties. , Conventionally, the electrochemical conversion between H + and H 0 has been extensively used in energy storage devices, such as fuel cells and H 2 storage systems. , Recently, H – has attracted considerable attention due to its novel applications in hydride-ion batteries, NH 3 synthesis catalysts, and photochromic materials. …”
mentioning
confidence: 99%